Internet of Things. IoT Infrastructures First International Summit, IoT360 2014, Rome, Italy, October 27-28, 2014, Revised Selected Papers, Part II - Giaffreda, Raffaele; Cagáňová, Dagmar; Li, Yong.; Riggio, Roberto; Voisard, Agnès; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The two-volume set LNICST 150 and 151 constitutes the thoroughly refereed post-conference proceedings of the First International Internet of Things Summit, IoT360 2014, held in Rome, Italy, in October 2014. This volume contains 30 revised full papers carefully reviewed and selected from 51 submissions at the following three conferences: the First International Conference on Mobility and Smart Cities, Mobility IoT 2014; the First International Conference on Software-Defined and Virtualized Future Wireless Networks, SDWN 2014; and the First International Conference on Safety and Security in Internet of Things, SaSeIot 2014. This volume also includes 13 special contributions from recognized experts. The papers in this volume are dedicated to infrastructure-based solutions that will support the deployment of IoT services and applications in the future. They cover the following topics: sustainable solutions to the mobility and smart cities agenda; software defined techniques for supporting more flexible use of wireless and wireless sensor networks; opportunities and risks related to the safety and security in the IoT domain.
Challenges and Unwanted Features of the Smarter Cities Development -- Multicultural Collaborative Team Working as a Driver for Innovation in the Slovak Automotive Sector -- Evaluation of more Economical Collection and Removal of Old Vehicles -- Rating attractiveness of sectoral environment- performance indicators -- Collective Creativity: Utilizing the Potentials of Multimodal Environments -- Strategic Management in SMEs in Selected European Countries -- Cities Auditing Model -- Smart Housing in Sustainable Development -- Parking Zero -- Information of rail freight transport by applying RF identification technology -- Smart City Vehicular Mobile Sensor Network 12 Modeling transportation preferences of urban residents. -- Extracting Meaningful User Locations from Temporally Annotated Geospatial Data -- Development of Autonomous Wheelchair for Indoor and Outdoor Traveling -- Safety and privacy perceptions in public spaces: An empirical study on user requirements for city mobility -- A study on Context Information Collection for Personal Mobile Device Identification in BYOD and Smart Work -- Iterative Design of a Sensor Network for the Evaluation of Pedestrian Facility Design using Agent-Based Simulations -- Introducing Community Awareness to Location-Based Social Networks -- Motivating Citizens to Contribute to the Smart City: A Public Safety Case Study -- What makes people change their preferences in public transportation – Opinions in different User Groups -- Laypeople’s perspectives on electromobility. A focus group Study -- Integrating the “E” in public transport Information and communication needs for electromobility -- Application for a personal mobility sharing system using two-wheeled self-balancing vehicles -- Multi-agent Simulator for Personal Mobility Vehicle Sharing -- The Added Value of a New, Innovative Travel Service: Insights from the UbiGo Field Operational Test in Gothenburg, Sweden -- On the Design of a Cost-Effective and Lightweight People Counting Sensor -- Smart Tourist - Passive Mobility Tracking through Mobile Application -- Understanding the Impact of Data Sparsity and Duration for Location Prediction Applications -- Cognitive Internet of Things: A Unified Perspective -- Secure Communication over Software-Defined Networks -- Integrating WMN based mobile backhaul with SDN control -- Energy Impact of Heterogeneous Wireless Networks on Mobile Devices -- An adaptive channel utilization method with traffic balancing for multi-hop multi-channel wireless backbone network -- Towards Active Charging for Software Defined Wireless Networks -- Optimal backhaul resource management in wireless-optical converged networks -- DOOR: A Data Model for Crowdsourcing with Application to Emergency Response -- Security Perspectives for Collaborative Data Acquisition in the Internet of Things -- The Role of the Internet of Things in Network Resilience -- NFC Peer To Peer Secure Services For Smart Cities.
Keywords: Computer communication systems; Application software; Special purpose computers; Computer Communication Networks; Information Systems Applications (incl. Internet).; Special Purpose and Application-Based Systems